Surveying support for child and youth political participation in Australia and New Zealand. Issue 5 (4th July 2019) - Phillips, Louise Gwenneth; Ritchie, Jenny; Perales, Francisco
ABSTRACT: Recent decades have witnessed increased empirical and policy interest in children's citizenship, particularly since the ratification of the United Nations Declaration of Children's Rights. However, support for children's active citizenship is often hindered by the pervasiveness of discourses that characterise children as innocent, developing, and free from responsibility. Public and governmental decision-making largely excludes children's consultation and contributions, often determined by age alone. To quantifiably assess the amount of public support for children's political participation, we commissioned a Likert scale survey question on degrees of support for children and youth (across four age groups between 3 and 18 year olds) having the opportunity to influence government decisions, in the Australian and New Zealand 2016 versions of the International Social Survey Programme (ISSP). Analysis of responses to this question in relation to demographic survey data indicate variation in preferences for different age groups, and that age, gender, and political party preference of respondents were variables of significance for both nations. These variables point to potential predictors of attitudes toward political participation of children and youth which have relevance for policymakers and educators in relation to provision of programmes that will increase the engagement of children and youth in government decision-making.